2015
DOI: 10.1128/jb.02625-14
|View full text |Cite
|
Sign up to set email alerts
|

Abbreviated Pathway for Biosynthesis of 2-Thiouridine in Bacillus subtilis

Abstract: The 2-thiouridine (s 2 U) modification of the wobble position in glutamate, glutamine, and lysine tRNA molecules serves to stabilize the anticodon structure, improving ribosomal binding and overall efficiency of the translational process. Biosynthesis IMPORTANCEThe 2-thiouridine (s 2 U) modification of the wobble position in glutamate, glutamine, and lysine tRNA is conserved in all three domains of life and stabilizes the anticodon structure, thus guaranteeing fidelity in translation. The biosynthesis of s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 39 publications
4
61
0
Order By: Relevance
“…The Bacillus subtilis ThiI appears to be a dedicated protein in s 4 U biosynthesis and it is not required for thiamine generation [165]. Interestingly, B. subtilis contains four cysteine desulfurases and evidence thus far has demonstrated that each pairs with a dedicated sulfur transferase for specific thiocofactor generation [68,72,166]. Formation of s 4 U, in particular, is accomplished by the cysteine desulfurase NifZ, the coding sequence of which is found immediately upstream of thiI .…”
Section: Biosynthesis Of Thionucleosides In Bacterial Trnamentioning
confidence: 99%
See 1 more Smart Citation
“…The Bacillus subtilis ThiI appears to be a dedicated protein in s 4 U biosynthesis and it is not required for thiamine generation [165]. Interestingly, B. subtilis contains four cysteine desulfurases and evidence thus far has demonstrated that each pairs with a dedicated sulfur transferase for specific thiocofactor generation [68,72,166]. Formation of s 4 U, in particular, is accomplished by the cysteine desulfurase NifZ, the coding sequence of which is found immediately upstream of thiI .…”
Section: Biosynthesis Of Thionucleosides In Bacterial Trnamentioning
confidence: 99%
“…Interestingly, in B. subtilis and in several other Gram-positive species missing tus genes, an IscS-like cysteine desulfurase gene ( yrvO ) is located in the same genomic region, and commonly directly upstream, of mnmA . Experimental characterization of B. subtilis YrvO and MnmA both in vivo and in vitro demonstrated that these two proteins are the sole requirements for s 2 U formation in this bacterium [72]. It is worth noting that the B. subtilis genome encodes a rhodanese protein (YrkF) with homology to TusA which is a competent sulfur acceptor of YrvO, but inactivation of yrkF leads to no changes in s 2 U levels [72,174].…”
Section: Biosynthesis Of Thionucleosides In Bacterial Trnamentioning
confidence: 99%
“…Notably, the rhodanese homology domain (RHD) that contains the catalytic Cys456, which carries the persulfide, is absent in many bacteria [8,45]; therefore, the sulfur transfer mechanism of RHD-lacking ThiI remains unanswered. The genome of B. subtilis encodes four functionally active cysteine desulfurases: SufS, NifZ, NifS, and YrvO [50]. Among them, the nifZ gene is adjacent to the thiI gene without RHD.…”
Section: Fe–s Cluster-dependent and Independent Trna Thiolation Prmentioning
confidence: 99%
“…Recently, a truncated pathway of s 2 U34 biosynthesis has been revealed in B. subtilis [50]. In this bacterium, the intermediate sulfur carries (TusA/BCD/E) are missing (Figure 4B).…”
Section: Fe–s Cluster-dependent and Independent Trna Thiolation Prmentioning
confidence: 99%
See 1 more Smart Citation